The publics of design: Challenges for design research and practice. (May 2022) - Matthews, Ben; Doherty, Skye; Johnston, Jane; Foth, Marcus
Abstract : The notion of 'publics' has emerged as a frame for rethinking the relationships between design practices and the communities affected by design. This paper explores two facets of the intersection of design and publics. First, we examine the notion of designing for public interests with an understanding of publics as multiple, conflicting and varied. Second, with reference to the Australian context, we reflect on different ways design communities can identify and support the formation of publics as a pivotal next step to more effectively serve its own interests and values, including the urgent enactment of social change. Our discussion identifies four sets of tensions that we offer as provocations for constructive and ongoing engagement by the design community at large to inform the process of designing for our own publics. Highlights: Reviews interdisciplinary scholarship on publics and public interests. Maps Australia's design industry associations to identify publics' challenges and opportunities. Identifies arising tensions across distinctions such as fragmentation or pluralism of interests. Asks design researchers critical questions about advocacy and unionisation. Invites discussion about how design communities can foment their own publics.